Analysis of the thermal behavior of gravure inks: comparing experimental results and numerical methods - Naskar, Shilpi; Paul, Kanai Chandra; Pal, Arun Kiran (Journal of Print and Media Technology Research, 2023)
Gravure inks are frequently applied in multiple layers as prints on packaging material. Besides giving some information about the product, the printed ink film can be used also for protection. The compound printed layer of different colored gravure inks (of equal thickness) plays an important role in protecting the product contained within the package from external atmospheric conditions. For example, heat transfer either from the outside or the inside of the package can be controlled by a properly designed ink film combination on the package. The color inks generally used are specialty white, standard yellow, magenta and cyan, together with black, applied consecutively. If these ink coatings are not long-lasting, or the system is not properly designed, this may lead to failure to protect the packaged product due to unwanted transfer. In the present investigation, the thermal properties of free films of different colored inks were measured individually and also in combination to assist in the design of appropriate ink layers on packaging leading to extended shelf-life for the product. The measured thermal properties are thermal conductivity, specific heat and the coefficient of linear expansion. Further, the thermal contact resistances of different color combinations, contact surface temperatures and thermal stress developed in the coating were determined using an algebraic method. A finite element method was also adopted for determining the contact surface temperature and thermal stresses developed. These numerical results were compared with the experimental findings. It was found that the heat transfer rate either from the package or from the outside will be much lower if the thicknesses of all the ink layers are equal. Also, it is proposed that if the coatings of inks are printed in the order of WKCMY, the protection of the product will be optimal.